The solute carrier family 7 member 11 (SLC7A11) is regulated by LH/androgen and required for cystine/glutathione homeostasis in mouse Sertoli cells. (1st June 2022) - Liu, Zhenghui; Wang, Huizen; Larsen, Mark; Gunewardana, Sumedha; Cendali, Francesca I.; Reisz, Julie A.; Akiyama, Haruhiko; Behringer, Richard R.; Ma, Qianyi; Hammoud, S. Sue; Kumar, T. Rajendra
Abstract: Luteinizing hormone (LH) stimulates testosterone production from Leydig cells. Both LH and testosterone play important roles in spermatogenesis and male fertility. To identify LH - and testosterone - responsive transporter genes that play key roles in spermatogenesis, we performed large-scale gene expression analyses on testes obtained from adult control and Lhb knockout mice. We found a significant reduction in cystine/glutamate transporter encoding Slc7a11 mRNA in testes of Lhb null mice. We observed that Slc7a11 /SLC7A11 expression was initiated pre-pubertally and developmentally regulated in mouse testis. Immunolocalization studies confirmed that SLC7A11 was mostly expressed in Sertoli cells in testes of control and germ cell-deficient mice. Western blot analyses indicated that SLC7A11 was significantly reduced in testes of mutant mice lacking either LH or androgen receptor selectively in Sertoli cells. Genetic and pharmacological rescue of Lhb knockout mice restored the testicular expression of Slc7a11 comparable to that observed in controls. Additionally, Slc7a11 mRNA was significantly suppressed upon Sertoli cell/testicular damage induced in mice by cadmium treatment. Knockdown of Slc7a11 in vitro in TM4 Sertoli cells or treatment of mice with sulfasalazine, a SLC7A11 inhibitor caused a significant reduction in intracellular cysteine and glutathione levels but glutamate content remained unchanged as determined by metabolomic analysis. Knockdown of Slc7a11 resulted in compensatory upregulation of other glutamate transporters belonging to the Slc1a family presumably to maintain intracellular glutamate levels. Collectively, our studies identified that SLC7A11 is an LH/testosterone-regulated transporter that is required for cysteine/glutathione but not glutamate homeostasis in mouse Sertoli cells. Highlights: Expression analysis on  Lhb  knockout mouse testis samples identified  Slc7a11  is the most significantly suppressed mRNA encoding a transporter. SLC7A11 expression is developmentally regulated and SLC7A11 is localized to mouse Sertoli cells within testis tubules. Genetic and pharmacological rescue of Lhb null mice restored SLC7A11 expression in testis. SLC7A11 expression is compromised in Sertoli cells of cadmium-induced testicular injury. Knockdown of  Slc7a11  or inhibition of SLC7A11 activity resulted in reduction in intracellular cysteine/GSH levels.